Big bad banks? : the impact of u.s. branch deregulation on income distribution - Beck, Thorsten, 1967- 1967- (NBER working paper series, 2007)
"Policymakers and economists disagree about the impact of bank regulations on the distribution of income. Exploiting cross-state and cross-time variation, we test whether liberalizing restrictions on intra-state branching in the United States intensified, ameliorated, or had no effect on income distribution. We find that branch deregulation lowered income inequality. Deregulation lowered income inequality by affecting labor market conditions, not by boosting the business income of the poor, nor by enhancing educational attainment. Reductions in the earnings gap between men and women and between skilled and unskilled workers account for the bulk of the explained drop in income inequality"--National Bureau of Economic Research web site